Carpal tunnel release: Safe and simple identification of the flexor retinaculum based on superficial anatomical landmarks. Issue 4 (25th March 2017) - Hohenberger, G.M.; Maier, M.J.; Grechenig, C.; Schwarz, A.M.; Matzi, V.; Weiglein, A.H.
Abstract : The aim of our study was to project the borders of the flexor retinaculum (FR) onto superficial landmarks since its insufficient splitting is the most common reason for persistence of symptoms after carpal tunnel release. In 60 hands the radial and ulnar styloid processes were linked by a horizontal line and a longitudinal line was laid through the ring finger's radial side. These were intersected resulting in the reference point "A" on the forearm. As the second basing point "B", the radial margin of the ring finger at the palmar digital crease was chosen. Measurement of the FR was carried out with regard to the reference points. The proximal margin of the FR was located at 4% of the reference line A‐B starting from point A and extended up to 52% of this total length. Results indicate that splitting alongside the proximal half of line A‐B divides the FR completely. Clin. Anat. 30:512–516, 2017. © 2017 Wiley Periodicals, Inc.